Visual motion interferes with lexical decision on motion words. - Meteyard, L; Zokaei, N; Bahrami, B; Vigliocco, G (2008)
Embodied theories of cognition propose that neural substrates used in experiencing the referent of a word, for example perceiving upward motion, should be engaged in weaker form when that word, for example 'rise', is comprehended [1-3]. This claim has been broadly supported in the motor domain (for example [4,5]), whilst evidence is supportive, but less clear cut, for perception (for example [6-8]). Motivated by the finding that the perception of irrelevant background motion at near-threshold, but not supra-threshold, levels interferes with task execution [9], we assessed whether interference from near-threshold background motion was modulated by its congruence with the meaning of words (semantic content) when participants completed a lexical decision task (deciding if a string of letters is a real word or not). Reaction times for motion words, such as 'rise' or 'fall', were slower when the direction of visual motion and the 'motion' of the word were incongruent - but only when the visual motion was at near-threshold levels (supporting [9]). When motion was supra-threshold, the distribution of error rates, not reaction times, implicated low-level motion processing in the semantic processing of motion words. As the perception of near-threshold signals is not likely to be influenced by strategies [9], our results support a close contact between semantic information and perceptual systems. © 2008 Elsevier Ltd. All rights reserved.